Issues faced by adolescents living with HIV/AIDS in shelter homes in Malaysia - Lourdunathan, Pamilia; Rahman, Shukran Abdul; Mohamad, Mardiana; Alwi, Azlin (2018)
UNICEF Malaysia has found that adolescents living with HIV/AIDS face several emotional, behavioural and social problems. Based on past literature, the result of these incidences has led to a lower well-being in these aspects. As the stage of adolescence is filled with change, inner growth, and sometimes conflict, adolescents coping with HIV face an added stressor as they strive to grow emotionally, behaviourally and socially. Given the lack of studies investigating these factors in a Malaysian setting, the present study seeks to fill this gap in research by identifying the issues facing adolescents with HIV. The main participants involved are namely: (1) 30 Malaysian adolescents with HIV from shelter homes; the personnel of the shelter homes comprising the: (2) programme coordinators; (3) staff; and (4) volunteers of the shelter homes, recruited via purposive sampling. Focus group discussions were conducted with the adolescents with HIV while semi-structured interviews were conducted with the personnel of the shelter homes. Thematic analysis was utilized in analysing findings through several themes. The findings indicated that the issues of adolescents living with HIV are Emotional issues, Behavioural issues, Social issues, Academic issues, Coping skills issues and Conative issues. These issues represent the main needs and problems faced by these adolescents.